Principles and practices of preventing and controlling rubber diseases in Sri Lanka - Jayasinghe C K (Bulletin of the Rubber Research Institute of Sri Lanka, 2001)
Rubber plants in Sri Lanka are susceptible to several diseases of economic importance. The most damaging canopy diseases are the leaf falls caused by the fungi Corynespora, Oidium, Phytophthora and Colletotrichum. Significant root and panel diseases include white root and black stripes respectively. The yield losses caused by these diseases are a key factor affecting the national productivity. In this presentation principles and disease management strategies are reviewed emphasizing current practices in Sri Lanka. Importance of the adaptation of correct cultural practices and use of the genetic resistance in disease management have been highlighted, as rubber is a marginally profitable crop today.
Keywords: Biological control; Chemical control; Correct cultural practices; Disease management; Hevea brasiliensis; Plant quarantine; Resistant clones